Serum matrix metalloproteinase-8, tissue inhibitor of metalloproteinase and myeloperoxidase in ischemic stroke - Palm, Frederick; Pussinen, Pirkko J.; Safer, Anton; Tervahartiala, Taina; Sorsa, Timo; Urbanek, Christian; Becher, Heiko; Grau, Armin J. (Atherosclerosis, 2018)
Background and aims - Matrix metalloproteinase (MMP)-8 and myeloperoxidase (MPO) may contribute to cerebral damage in acute ischemic stroke. We tested the hypothesis that levels of MPO, MMP-8 and the ratio between MMP-8 and its regulator, tissue inhibitor of metalloproteinase (TIMP-1), are increased in acute ischemic stroke and its etiologic subgroups and they correlate with stroke severity. - Methods - In a cross-sectional case-control study, serum concentrations of MMP-8, MPO and TIMP-1 were assessed within 24h after admission in 470 first-ever ischemic stroke patients and 809 age- and sex-matched controls, randomly selected from the population. Odds ratios (OR) per decade of log transformed dependent variables were calculated and adjusted for age, sex and vascular risk factors. - Results - Levels of MMP-8 (OR 4.9; 95% CI 3.4-7.2), MMP-8/TIMP-1 ratio (3.0; 2.2-4.1) and MPO (6.6; 4.0-11.0) were independently associated with ischemic stroke. MMP-8 levels differed between etiologic stroke subgroups (p=0.019, ANOVA), with higher levels in cardioembolic stroke and stroke due to large vessel disease, and lower levels in microangiopathic stroke. MMP-8, MMP-8/TIMP-1 ratio and MPO (p < 0.001) concentrations showed positive associations with stroke severity independent of stroke etiology. - Conclusions - Concentrations of serum neutrophil markers are increased after ischemic stroke and associate with stroke severity and etiology. The value of these biomarkers in diagnostics and prognostics is worth being evaluated.